A Haptic Feedback Actuator Suitable for the Soft Wearable Device - Jiaqi Ma; Xiang Cheng; Pengfei Wang; Zhiwei Jiao; Yuan Yu; Meng Yu; Bin Luo; Weimin Yang (Applied Sciences, 2020)
Gaining direct tactile sensation is becoming increasingly important for humans in human–computer interaction fields such as space robot teleoperation and augmented reality (AR). In this study, a novel electro-hydraulic soft actuator was designed and manufactured. The proposed actuator is composed of polydimethylsiloxane (PDMS) films, flexible electrodes, and an insulating liquid dielectric. The influence of two different voltage loading methods on the output characteristics of the actuator was studied. The special voltage loading method (AC voltage) enables the actuator to respond rapidly (within 0.15 s), output a stable displacement in 3 s, and remain unchanged in the subsequent time. By adjusting the voltages and frequencies, a maximum output displacement of 1.1 mm and an output force of 1 N/cm2 can be rapidly achieved at a voltage of 12 kV (20 Hz). Finally, a haptic feedback system was built to control the robotic hand to perform gripping tasks in real time, and a more realistic tactile sensation could be realized, similar to that obtained when a human directly grabs objects. Therefore, the actuator has excellent portability, robustness, rapid response, and good compatibility with the human body for human–computer interaction.